Atypical recurrent kawasaki disease with retropharyngeal involvement: A case study and literature review - Rachel K Cason; Umakumaran P Ponniah; Elizabeth S Makil; Mary C Niu (Wolters Kluwer Medknow Publications, 2020)
Kawasaki disease (KD) is a systemic inflammatory condition primarily affecting young children. We present an adolescent male with two episodes of complete KD between the age of 2 and 14 years. At age 14, he presented with findings suggestive of a retropharyngeal abscess. This was later determined to be a recurrence of KD, diagnosed after the development of coronary artery aneurysms. Our case reinforces the role of maintaining a high index of suspicion for KD, both in patients with prior KD episodes and in those with persistent fever who do not fulfill the diagnostic criteria for typical KD. This is particularly important for patients presenting with atypical symptoms not commonly associated with KD, such as inflammation of the retropharyngeal and parapharyngeal spaces.